Embodying biopolitically discriminate borders: teachers' spatializations of race. Issue 1 (2nd January 2022) - Martschenko, Daphne
ABSTRACT: Borders are constructs that shape our understandings of our societies, communities, and the world. Geospatial borders draw distinctions between neighborhoods and schools that are deemed 'worthy' and 'unworthy' of economic, social, and political investment. This paper employs the theoretical framework of 'discriminate biopower' to argue that geospatial borders produce a 'socio-political invisibility' linked to race and racial inequality. Through focus group discussions with kindergarten – grade eight educators in the Chicago metropolitan area of the United States, this paper provides evidence of how understandings of race are spatially applied by teachers. Findings suggest that teachers located and conflated individuals and racial groups with physical locations, demonstrating how spatial borders and the practice of bordering function as a biopolitical and segregationist way to understand race and power.